Morphophysiological response of the thyroid gland of female Mus musculus exposed to essential oils (bioactive compounds) extracted from Egletes viscosa and Lippia schauerian (International Seven Journal of Multidisciplinary, 2023)
The tick Rhipicephalus linnaei (Audouin, 1826), popularly known as the brown dog tick, is of medical and veterinary importance because it transmits several pathogens that cause diseases which are relevant to public health and, consequently, significant economic losses. Previous studies have shown that acaricides that use synthetic active ingredients leave harmful residues in the environment and cause problems for non-target organisms, which include hosts in general. For these reasons, new strategies and control methods, such as biological approaches, vaccines, and bioactive compounds from plants, have been studied. In the present study, the action of essential oils extracted from Egletes viscosa and Lippia schaueriana, both native to Brazil, were evaluated. Despite having proven effectiveness as acaricides (against this species of ticks), studies on the effects they have on hosts (here simulated by female Mus musculus) had not yet been performed. The unprecedented results found here showed that, in treatment group T1 (female mice exposed to L. schaueriana oil), there were morphological changes in the thyroid that indicated that these glands would also have the functions of synthesis/transformation of the colloid into thyroid hormones physiologically compromised. There were changes in the morphology of follicular cells (from cuboidal to squamous) and cytoplasmic vacuolation. The colloid inside the follicles did not always appear homogeneous, and in many of them, a fine granulation was noticed, suggesting changes in the pre-hormone. In treatment group 2 (females exposed to E. viscosa oil), the follicular cells in the vast majority of follicles also lost their cuboidal shape and became squamous, and their nuclei changed from rounded to flattened and pyknotic. The rounded morphology of the follicles became irregular, causing disorganization of the follicular cells, and the interstitial spaces left between the follicles were filled by connective tissue. Therefore, these results make it clear that the exposure of female mice (simulating tick hosts) to essential oils of E. viscosa and L. schaueriana at a concentration of 50mg/mL caused morphophysiological changes in the thyroid gland of these subjects, which lead to the loss of organ function, and called attention to the importance of the careful use of acaricides even if they are naturally sourced. DOI:https://doi.org/10.56238/isevmjv2n2-004